PEMBELAJARAN TEMA DIRI SENDIRI BERMEDIA KOMIK UNTUK MENINGKATKAN PENGUASAAN KOSATAKA ANAK TUNARUNGU DI SLB - HIDAYATI, NURUL (Jurnal Pendidikan Khusus, 2017)
Abstract Mastering vocabulary to hearing impairment children was one of the important factors in learning. To be able to learn the learning material of own self theme, the hearing impairment children required to enhance their mastering vocabulary. Hearing impairment children were those who lost their hearing either partly (hard of hearing) or whole (deaf) which caused their hearing did not have functional value in the daily life. It caused the hearing impairment children required help to understand new words in either learning or daily life. Therefore, it needed a media which could describe the words in the form of visual to facilitate the hearing impairment children understanding the learning material of own self theme. The purpose of this research which had done was to know whether in this learning own self theme with comic media there was enhancement of vocabulary mastery to hearing impairment children in SLB Negeri Gedangan Sidoarjo or not. This research used experiment kind i.e. one group pre test – post test with 01 x 02 pattern. In this research, the test was done before and after giving treatment to 7 samples. In this way, it could be known the difference of the children’s ability before and after giving treatment. From the result of data analysis it was found that the average post test was greater than the average pre test which indicated there was enhancement of mastering vocabulary to hearing impairment children after learning using comic media to own self theme. This research result indicated that T counted value with n 7 was 1 and it was smaller than T value in Wilcoxon’s table 0,05 i.e. 2 so it could be concluded that Ho was refused and Ha was accepted, and it was stated that there was enhancement of mastering vocabulary to hearing impairment children in learning own self theme with comic media in SLB Negeri Gedangan Sidoarjo.     Keywords: Learning own self theme, comic media